1995
DOI: 10.1029/95jd01250
|View full text |Cite
|
Sign up to set email alerts
|

Ozone oxidation of sulfur in sea‐salt aerosol particles during the Azores Marine Aerosol and Gas Exchange experiment

Abstract: Sea‐salt aerosol particles in the lowest tens of meters above the ocean are, typically, more than three‐fourths water on a volume basis. Calculations herein indicate that aqueous‐phase conversion of sulfur dioxide dissolved in the water associated with sea‐salt particles (sea‐salt aerosol water) supported the production of 2–8 nmol m−3 of nonsea‐salt sulfate (nssSO4=) during the Marine Aerosol and Gas Exchange (MAGE) experiment intensives. This production is based on ozone oxidation of dissolved SO2 in sea‐sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 29 publications
(17 reference statements)
7
41
0
Order By: Relevance
“…This is consistent with a slow reaction of S(IV) in the water layer. Sea salt is known to contain buffering species such as carbonates which can react with dissolved S(IV) [Sievering et al, , 1992[Sievering et al, , 1995 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a slow reaction of S(IV) in the water layer. Sea salt is known to contain buffering species such as carbonates which can react with dissolved S(IV) [Sievering et al, , 1992[Sievering et al, , 1995 …”
Section: Resultsmentioning
confidence: 99%
“…Sulfur dioxide (SO2) in the marine boundary layer is oxidized in deliquesced sea salt aerosol with dissolved oxidants such as ozone and H202 to form S(VI) species Sievering et al, 1991Sievering et al, , 1992Sievering et al, , 1995 [Vogt et. al., 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone efficiently oxidizes SO2 in neutral or basic sea-salt aerosols [Sievering et al, 1995]. It has also been suggested that S(IV) is oxidized via a catalytic cycle [Mozurkewich, 1995;Sander et al, 1995].…”
Section: Participation In Liquid-phase Chemistrymentioning
confidence: 99%
“…Dissolved S(IV) is oxidized in the aqueous phase and on the surfaces of particles by a number of oxidants, such as H 2 O 2 , O 3 , HOCl, HOBr and O 2 catalyzed by metals and perhaps by chloride ions. [50][51][52][53][54][55]57,60,71,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] SO 2 can also be oxidized in the gas phase, mainly by OH, 96 to produce sulfuric acid which is then taken up by cloud droplets and particles; however, this is generally a minor pathway compared to aqueous oxidation. 16 In this work, we demonstrate the application of DRIFTS to studying the uptake and oxidation of gaseous SO 2 at 50% relative humidity (RH) on NaCl-MgCl 2 Á 6H 2 O salt mixtures that have been previously reacted with OH formed by the photolysis of O 3 in the presence of water vapor.…”
Section: Introductionmentioning
confidence: 99%